Evaluation of environmental education centres - A research design for the case study method - Salomé Schulze (Environmental Association of Southern Africa, 1992)
A research design for evaluation of environmental education centres by means of the case study method is explained. This method may be divided into four stages: selecting a case, gathering data (by studying documents and archival records, conducting interviews, direct observation and by means of questionnaires), analysing the data and writing the report. Validity, reliability and some ethical principles when writing the report are also mentioned.